Importance of antibiotics in the treatment of Covid-19 (Research, Society and Development, 2020)
Antibiotics are being used as an experimental treatment in patients infected with coronavirus, in some patients there was an improvement in signs and symptoms and a reduction in viral load. Based on these facts, studies are being conducted to prove the efficacy of antibiotics, especially macrolides, due to their ability to act at the site of infection, having immunomodulatory action, also having activity against intracellular pathogens. The aim of this study is to verify in the current literature the importance of antibiotics in the treatment of COVID-19 carriers. The methodology used was an integrative review study in lilacs and pubmed databases. The results showed that antibiotics, especially macrolides, showed positive results regarding the reduction of viral load and immunomodulatory function. However, the small number of studies conducted and few patients analyzed are reflections of a challenge to be faced, . In addition, there is a need to understand the mechanisms of action and drug interactions at the molecular level, and phylogenetic studies are also needed.